2016
DOI: 10.1371/journal.pone.0162667
|View full text |Cite
|
Sign up to set email alerts
|

GM-CSF Down-Regulates TLR Expression via the Transcription Factor PU.1 in Human Monocytes

Abstract: Toll-like receptors (TLR) are crucial sensors of microbial agents such as bacterial or viral compounds. These receptors constitute key players in the induction of inflammation, e.g. in septic or chronic inflammatory diseases. Colony-stimulating factors (CSFs) such as granulocyte-macrophage-CSF (GM-CSF) or granulocyte-CSF (G-CSF) have been extensively investigated in their capacity to promote myelopoiesis in febrile neutropenia or to overcome immunosuppression in patients suffering from sepsis-associated neutro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 31 publications
0
15
0
2
Order By: Relevance
“…The mechanisms involved in downregulation or upregulation of TLRs are far from being fully understood. Authors have shown the involvement of transcription factors, miRNAs, cytokines, and proteins ( Sadeghi et al, 2016 ; Liu et al, 2017 ), but so far, it is not clear how a highly endotoxic molecule receptor is upregulated in the presence of LPS. Both TLR-2 and TLR-4 receptors can activate the MyD88 pathway, which involves the early activation of NF-κB.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms involved in downregulation or upregulation of TLRs are far from being fully understood. Authors have shown the involvement of transcription factors, miRNAs, cytokines, and proteins ( Sadeghi et al, 2016 ; Liu et al, 2017 ), but so far, it is not clear how a highly endotoxic molecule receptor is upregulated in the presence of LPS. Both TLR-2 and TLR-4 receptors can activate the MyD88 pathway, which involves the early activation of NF-κB.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that the immunomodulatory drug pomalidomide down-regulates PU.1, which is one mechanism by which pomalidomide can be used to treat multiple myeloma 17 19 . To evaluate the effect of pomalidomide on expression and function of PU.1 in MCs, we treated LAD2 cells with pomalidomide.…”
Section: Resultsmentioning
confidence: 99%
“…TLRs have been shown to be essential for the activation of monocytic cells, and it plays a role in the production of GM-CSF by activating the transcription factor PU.I, which plays a fundamental role in this lineage [82]. In dendritic cells derived from macrophages, TLRs are involved in the synthesis of IL-7, which is an essential interleukin for the maintenance of LT CD8+ [75].…”
Section: Action Mechanism Of Caseins To Induce Hematopoiesis and Immumentioning
confidence: 99%